Dinamika Pendidikan Karakter dalam Kajian Budaya Dan Psikologi Pendidikan - Sihar Pandapotan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
Indonesia focuses high attention on the educational aspect. This can be seen from the education system that is always being updated to keep up with the times. However, several social realities in Indonesia today show that on the other hand the moral crisis is also increasing. This certainly becomes a lameness in the world of education, especially in character education which is predicted as an idea that is able to create Indonesian national character. The journey of character education should be expected to be able to minimize the moral crisis but is still ignored. Character education is considered to be only the task of the school world, when in fact the social environment also plays a very important role in helping carry out character education in society. This is the dynamic in character education today. Whereas character education has actually been carried out by our forefathers and has been passed down through generations through the proverbial life, norms and customs which in cultural studies are known as Folklore. A cultural heritage in the form of oral, written, and movement is able to provide moral cultivation and character education. The research method in this paper is a form of literature study method. Examining and analyzing the dynamics of character education from the results of previous writings that focus on the study of cultural and educational psychology.